Optimization of 3D Printing Parameters Using the Taguchi Method to Improve Dimensional Precision - Martinus Bagus Wicaksono; Felix Krisna Aji Nugraha (Universitas Putra Indonesia YPTK Padang, 2022)
The combination of parameters in the product printing process with Polylactic Acid (PLA) material using the ANET ET4 PRO 3D printer is carried out to obtain optimal parameters to produce accurate dimensions in the printing process. The most popular type of 3D printer is the Fused Deposition Modeling (FDM) type, which uses melted plastic raw materials to form products. In the existing printing process, the accuracy of the dimension is the main problem owned by users of this 3D printer technology. Especially when these products have to be assembled into a mechanism. The resulting accuracy is greatly influenced by the selection of process parameters used during the printing process. The parameter optimization process using the Taguchi method was chosen because this method is very good at overcoming deviations from the target so that the best quality of the product can be achieved. The optimization process of this parameter will be carried out using a ring-shaped specimen with an outer diameter of 30 mm, an inner diameter of 20 mm, and a height of 20 mm. This deviation in the size of the inner diameter of the ring would be the reference for measuring the quality of the printed object. From the experiments, the most optimal level values for each factor were as follows: the Nozzle Temperature was 200 °C, the Bed Temperature was 62 °C, the Room Temperature was 34 °C, the Infill Percentage was 40%, the Layer Height was 0.25 mm, the Printing Speed was 20 mm⁄s.